2021
DOI: 10.3892/ijmm.2021.4873
|View full text |Cite
|
Sign up to set email alerts
|

CircUSP36 knockdown alleviates oxidized low‑density lipoprotein‑induced cell injury and inflammatory responses in human umbilical vein endothelial cells via the miR‑20a‑5p/ROCK2 axis

Abstract: The dysfunctions of human umbilical vein endothelial cells (HUVEcs) are important features of atherosclerosis (AS). circular RNAs (circRNAs) are regulators of a wide range of human diseases, including AS. The present study aimed to investigate the role of circUSP36 in the ectopic phenotype of HUVEcs and to provide evidence of the involvement of circUSP36 in the pathogenesis of AS. AS cell models in vitro were established using HUVEcs exposed to oxidized low-density lipoprotein (ox-LdL). cell viability, cell cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Furthermore, the potential of circUSP36 has been explored in the regulation of endothelial cell dysfunction. It has been proven that circUSP36 aggravates endothelial injury caused by ox-LDL by restraining cell proliferation, migration, invasion, and angiogenesis, while promoting apoptosis and inflammation [44][45][46][47]. In concert with these previous findings, this study demonstrated that circUSP36 was highly expressed in ox-LDLtreated endothelial cells than in the control group and that enforced expression of circUSP36 suppressed cell proliferation and migration in ox-LDL-treated endothelial cells.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, the potential of circUSP36 has been explored in the regulation of endothelial cell dysfunction. It has been proven that circUSP36 aggravates endothelial injury caused by ox-LDL by restraining cell proliferation, migration, invasion, and angiogenesis, while promoting apoptosis and inflammation [44][45][46][47]. In concert with these previous findings, this study demonstrated that circUSP36 was highly expressed in ox-LDLtreated endothelial cells than in the control group and that enforced expression of circUSP36 suppressed cell proliferation and migration in ox-LDL-treated endothelial cells.…”
Section: Discussionsupporting
confidence: 79%
“…Via targeting the miR-330-5p and further upregulating the expression of TLR4, the NF-κB pathway would be activated to regulate the inflammation response, oxidase stress, and cell apoptosis ( 36 ). The levels of vascular cell adhesion molecule 1 (VCAM1) and roundabout guidance receptor 1(ROBO1) was also upregulated with the miR-98-5p and miR-20a-5p downregulated and sponged by circ-USP36 in oxLDL-induced injuries, which could both accelerate the endothelial cell injury ( 37 , 38 ). However, differently, through absorbing the miR-637 to enhance WNT4, the circ-USP36 had been reported to attenuate the EC proliferation and migration in the oxLDL-induced injury ( 39 ).…”
Section: Oxldl and Endothelial Cell Dysfunctionmentioning
confidence: 99%
“…In addition, exosomes from platelets, vessel cells ( He et al, 2018 ; Bai et al, 2020b ), inflammatory adipocytes ( Wadey et al, 2019 ) and dendritic cells increased the level of inflammatory factors and recruited inflammatory cells and promoted their adhesion to the vessel wall, leading to a chronic inflammatory response process in AS. Multiple circRNAs (circ_0004104 ( Zhang et al, 2021a ), circular ANRIL ( Song et al, 2017 ), circTM7SF3 ( Wang and Bai, 2021 ), circUSP36 ( Miao et al, 2021 ) and so on) were upregulated in AS and demonstrated to induce vascular EC injury and oxidative stress and inflammation. Circ_GRN and Circ_CHFR were also upregulated in atherosclerotic serum and expedited the inflammation of human vascular muscle cells ( Zhuang et al, 2020 ; Li et al, 2021a ).…”
Section: Ev-circrnas In the Progression Of Asmentioning
confidence: 99%